Pelatihan Penggunaan dan Perawatan Mesin Pencuci Telur Asin Bagi UKM ‘Mak Ngat’ dipasar Rasamala Perumahan Srondol Wetan Kecamatan Bayumanik Kota Semarang - Trio Setiyawan; Riles Melvy Wattimena; Sugeng Irianto; Timotius Anggit K; Nurhidayati Nurhidayati; Hery Tristijanto; Avicenna An-Nizhami; Iman Mujiarto (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Semarang State Polytechnic as a tertiary institution implementing the Tri Darma of Higher Education through the 2023 Competitive Community Service program sees several problems faced by UMKM partners, where the service partner who collaborates with us is Mang Ngat UMKM, one of whose businesses is engaged in making salted eggs, where One of the problems faced is that there is no egg washing machine that replaces manual washing of salted eggs, but this problem can be resolved with the provision or donation of a salted egg washing machine in the first stage. The next problem faced by Mang Ngat UMKM service activity partners is that they require knowledge of the machine operation process according to procedures so that the operation is safer for the operator and the machine. Apart from that, Mang Ngat UMKM also need knowledge of the maintenance process for the salted egg washing machine so that the machine can last longer. long. With these problems, in the follow-up activities of Community Service to Mang Ngat UMKM after the provision or grant of egg washing machines, follow-up activities were carried out, namely by carrying out training on the operation and maintenance of salted egg washing machines at Mang Ngat UMKM in the Rasamala market, Srondol Wetan housing complex, Banyumanik sub-district, Semarang city, with After carrying out training on the operation and maintenance of salted egg washing machines, it is hoped that the salted egg washing machines can be operated safely by Mang Ngat UMKM and maintenance can be carried out properly so that the salted egg washing machines can increase their service life.